Language anxiety: understanding past research and new directions with d/Deaf, DeafBlind, and hard of hearing communities - Kim, Christina; Aichler, Laurel; Bridgett, Tiffany; Nicolarakis, Onudeah; Hanumantha Lacy, Shilpa; Sortino, Rachel; Kushalnagar, Poorna; Pizzie, Rachel (Frontiers in Psychology, 2025)
Language anxiety occurs when people associate negative emotional responses with using, expressing, or understanding language. In this review, we summarize past language anxiety research regarding specific language processes or subtypes: reading, writing, speaking, listening, and foreign language anxieties. Language anxiety is associated with poorer language proficiency and hinders learning and improving language skills. By conceptualizing language anxiety processes together, we identify common patterns and themes which will be vital for understanding how anxiety is detrimental to language performance. We discuss existing knowledge and propose applying theoretical framework names from another educational anxiety domain to more broadly understand language anxiety. These frameworks explain similar affective, cognitive, and behavioral relationships seen across subtypes of language anxiety. Past research suggests that some people are more likely to experience language anxiety and its detrimental effects on language. Through this review, we underscore the need for future directions to focus on individuals from diverse language backgrounds who are at greater risk for developing language anxiety. Social and linguistic factors, particularly in early life, foster negative emotional associations with and challenges to language acquisition. Future research collaborations with those who have lived experiences with language deprivation and language anxiety will clarify how emotion influences language development. We discuss how some d/Deaf, DeafBlind, and hard of hearing people have greater risk for developing language anxiety. Language anxiety is a prevalent, genuine barrier to learning and improving proficiency for deaf individuals who have difficulty acquiring language skills and experience adverse childhood communication experiences. Characterizing language anxieties toward signed and spoken languages will also clarify efforts to reduce anxiety for diverse language learners. Engaging underrepresented groups in language anxiety research can clarify how emotion plays a role in language development and identify groups that would benefit from future language anxiety-focused interventions. By focusing on and gaining a better understanding of emotional, diverse language experiences, we can build effective language anxiety interventions and improve language outcomes for all.